Evaluating Patient Safety Culture in Iraqi Community Pharmacies - Jasim, Basma S.; Y. Jamal, Mohammed (Iraqi Journal of Pharmaceutical Sciences, 2021)
Patient safety is the main issue in health care organization, the Agency for Healthcare Research and Quality defines it as, “freedom from accidental or preventable injuries produced by medical care. Thus, practices or interventions that improve patient safety are those that reduce the occurrence of preventable adverse events”. The purpose of this study was to evaluate Iraqi pharmacist perception about the culture of patient safety. As well as estimate whether safety is a principal issue in their pharmaceutical practice this study was carried out on 435 pharmacists who are working in community pharmacies in various Iraqi provinces. A survey was distributed via the internet during the period from May to June 2020. A community pharmacy questionnaire was used to evaluate the awareness of pharmacists regarding the culture of patient safety. A result of this study shows that the patient counseling field was the most positive one among the studied domains with score 68.8% of positive awareness and 70.4% of the pharmacists indicated that they inform patients with needed information about their new prescriptions. In contrast, staffing and work pressure scored the lowest positive response (36.55%). Although 66.7% of the participants stated they have the appropriate number of staff in their pharmacies to deal with the workload.